Relationship of Glycemic Control with Level of Blood Pressure amongst Type 2 Diabetic Patients - Ammarah Saeed, Zunera Jahanzeb, Uzma Batool, Samia Kauser, Mushtaq Muhammad, Nasir Mahmood (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Inadequate control of glycemia in type-II diabetic patients is an important community health issue and a risk factor for the progression of problems among diabetic patients. Hypertension is a common disease accompanying diabetes. Among patients with diabetes mellitus; high blood pressure is an important factor involved in poor glycemic control which has not been adequately assessed in Pakistan. Aim: The main goal was to evaluate the glycemic control status in type II diabetic patient depending on the basis of blood pressure levels. Place and Duration: In Medicine Department of Islamic International Hospital and Medical College, Islamabad for the duration of six months from January 2021 to June 2021. Methods: 220 adult patients >18 years of age with type-II diabetes mellitus were included. Patients with conditions such as liver cirrhosis, systemic infection, pregnant females, end-stage renal disease and those who were not observing diabetes treatment, counting exercise, dietary restrictions and medication, they were omitted from the anlaysis. By evaluating medical records; the patient’s demographic information was obtained which includes medical history, patient age, clinical history, gender, hypertension and type of DM in addition to the assessment of blood sugar level control. Statistical analysis was performed by using the SPSS 20.0. Results: The patients mean age was 58.10 ± 10.94 years with 35-80 years of age range. Of 220 patients, 145 (65.9%) had hypertension and 75 (34.1%) had normal blood pressure, and 7.72 ± 1.28 years was the patient’s mean duration of hypertension. The males have the HbA1c levels of 7.11 ±1.34 and 7.81 ±1.58 in females. In the hypertensive group of patients; mean HbA1c was higher significantly in comparison to the normal blood pressure group (p = 0.003). The HbA1c mean levels were also higher significantly among hypertensive patients with duration for over ten years (p = 0.04) and in subjects using diuretics (p = 0.03) and beta-blockers (p = 0.006) as an antihypertensive drug. Among patients with normal body mass index and nutritional recommendations, the mean (± SD) HbA1c in patients with hypertension was 5.13 ± 0.03 compared with patients with normal blood pressure (p = 0.00007). Conclusions: The control of Glycemia in type II diabetic patients is poor with hypertension. There is a complex relation of various factors, including gender, age, hypertension duration, and drugs that strongly effect control of glycemia among hypertensive patients and type-II diabetes mellitus. Keywords: Hypertension, Type 2 diabetes, HbA1c